Village Fund and Rural Poverty: Evidence from North Aceh, the Poorest Region in Aceh - Silvia Zahara; Irfan Zikri; Sofyan; Andi Sahriani Safitri (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2024)
The Indonesian government implemented the Village Fund policy 2014 to encourage development and reduce rural poverty. This study aims to analyze the impact of the Village Fund on poverty in North Aceh District. The research method uses descriptive analysis, focusing on the Village Fund variable, the poverty variable, and Direct Cash Assistance (BLT) as a representation of the number of poor people, and the Developing Villages Index (IDM) variable as a representation of poverty in the context of village development. The villages of Cot Girek, Pulo Dulang, Grong-Grong, Cot Trueng, and Meunasah Lhok were selected as case examples to provide a more comprehensive picture. The research found that during the 2018-2023 period, Village Fund allocations in North Aceh Regency fluctuated, poverty rates decreased, and village development increased significantly. Within five years, more than 50% of villages in North Aceh changed their status from underdeveloped to developing villages. Fluctuations in the Village Fund also occurred in the five research villages, and there was an increase in the number of poor BLT recipients in several villages. The five villages continued to experience holistic village development, including social, economic, and ecological improvements.